Hospitalisation time is associated with weight gain in forensic mental health patients with schizophrenia or bipolar disorder. (3rd January 2023) - Pedersen, Anne Louise Winkler; Gildberg, Frederik Alkier; Hjorth, Peter; Højlund, Mikkel; Andersen, Kjeld
Abstract: Introduction: People with mental disorders have higher mortality from lifestyle diseases than the general population. Forensic mental health patients (FMHPs) are often hospitalised for longer periods of time than non-FMHPs. Thus, hospitalisation may have a greater effect on the risk of lifestyle diseases in FMHPs. Objective: Investigate associations between proportional hospitalisation time (PHT) and change in body weight or other cardiometabolic risk factors among FMHPs. Methods: Retrospective cohort study including all FMHPs with schizophrenia or bipolar disorder, prescribed antipsychotics, and treated between 01 January 2016 and 06 April 2020 in the Region of Southern Denmark either in forensic units or as outpatients. Associations between PHT and, respectively, primary and secondary outcomes were analysed using linear regression. PHT was determined between each measurement of the outcomes as the number of days hospitalised divided by the total number of days within the time-period. The primary outcome was weight change and secondary outcomes were change in waist circumference (WC), blood pressure, estimated average glucose (eAG), HDL, LDL, total cholesterol, and triglycerides. Analyses were adjusted for gender, age, smoking, and antipsychotics. Results: The cohort included 490 FMHPs, of which 440 were diagnosed with schizophrenia. PHT had a significant positive dose-response association with weight change, with an estimated difference of +4.0 kg/year for FMHPs who were hospitalised 100% of the time, compared to FMHPs who were exclusively treated as outpatients. The association interacted with baseline BMI. From the secondary outcomes, the association with PHT was only statistically significant for WC. Conclusions: PHT was positively associated with weight gain.